Global Exponential Stability of a Discrete-Time Rayleigh System with Delays - Bangyu Shen (Discrete Dynamics in Nature and Society)
This paper deals with the problem of global exponential stability for a discrete-time Rayleigh system with delays. By using the mathematical induction method, some sufficient conditions are proposed for the global exponential stability of the discrete-time Rayleigh system. Finally, a numerical example is given to illustrate the effectiveness and application of the obtained results.